2017
DOI: 10.1038/ncb3626
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 promotes degradation of stalled replication forks by recruiting MUS81 through histone H3 trimethylation

Abstract: The emergence of resistance to poly-ADP-ribose polymerase inhibitors (PARPi) poses a threat to the treatment of BRCA1 and BRCA2 (BRCA1/2)-deficient tumours. Stabilization of stalled DNA replication forks is a recently identified PARPi-resistance mechanism that promotes genomic stability in BRCA1/2-deficient cancers. Dissecting the molecular pathways controlling genomic stability at stalled forks is critical. Here we show that EZH2 localizes at stalled forks where it methylates Lys27 on histone 3 (H3K27me3), me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
284
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(304 citation statements)
references
References 42 publications
19
284
1
Order By: Relevance
“…We also identified the CHD4interacting protein ZFHX3 (Chudnovsky et al, 2014), whose depletion we found enhanced cisplatin resistance in PEO1 cells ( Figure 3C). Moreover, in BRCA2 deficient ovarian cancers, low mRNA levels of ZFHX3 predicted poor tumor-free survival ( Figure 3D) as previously found for CHD4, EZH2, and FEN1 (Guillemette et al, 2015;Meghani et al, 2018;Rondinelli et al, 2017). Strikingly, we observed that depletion of ZFHX3 or FEN1, or EZH2 inhibition, increased replication in the presence of HU ( Figure 3E), as found for CHD4 depletion.…”
Section: Moreover In Agreement With Increased Replication Track Lengsupporting
confidence: 86%
See 1 more Smart Citation
“…We also identified the CHD4interacting protein ZFHX3 (Chudnovsky et al, 2014), whose depletion we found enhanced cisplatin resistance in PEO1 cells ( Figure 3C). Moreover, in BRCA2 deficient ovarian cancers, low mRNA levels of ZFHX3 predicted poor tumor-free survival ( Figure 3D) as previously found for CHD4, EZH2, and FEN1 (Guillemette et al, 2015;Meghani et al, 2018;Rondinelli et al, 2017). Strikingly, we observed that depletion of ZFHX3 or FEN1, or EZH2 inhibition, increased replication in the presence of HU ( Figure 3E), as found for CHD4 depletion.…”
Section: Moreover In Agreement With Increased Replication Track Lengsupporting
confidence: 86%
“…Thus, we performed quantitative mass spectrometry proteomics comparing the CHD4-interactome between BRCA2 deficient vs proficient cells after cisplatin treatment ( Figure 3A). In BRCA2 deficient PEO1 cells, CHD4 interacted with several proteins known, when lost, to confer chemoresistance without restoring HR, including PARP1, EZH2, and FEN1 ( Figure 3B) (Guillemette et al, 2015;Meghani et al, 2018;Rondinelli et al, 2017). We also identified the CHD4interacting protein ZFHX3 (Chudnovsky et al, 2014), whose depletion we found enhanced cisplatin resistance in PEO1 cells ( Figure 3C).…”
Section: Moreover In Agreement With Increased Replication Track Lengmentioning
confidence: 74%
“…Beyond their role in DSB repair via HRR, BRCA1 and BRCA2 occupy an important role in limiting access of nucleases (such as MRE11 ) to single-strand DNA at stalled replication forks, thereby leading to replication fork protection. Recently, loss of PTIP , CHD4 , and EZH2 have been identified as a mechanism of resistance in BRCA2 -deficient cells (Ding et al, 2016; Guillemette et al, 2015; Ray Chaudhuri et al, 2016; Rondinelli et al, 2017). Specifically, deficiency in PTIP and CHD4 impedes recruitment of MRE11 , thereby protecting stalled replication forks from nucleolytic degradation in BRCA2 mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the mechanism of platinum and PARPi resistance in BRCA2 -mutated carcinomas has been a challenge as HRR is not restored in cells expressing mutant BRCA2 . However, few recent studies have revealed that BRCA2 mutant carcinomas might still develop platinum and PARPi resistance without restoration of HRR proficiency via a complex mechanism where stalled DNA replication fork is protected from degradation by nucleases by downregulation of proteins such as PTIP , CHD4 , or EZH2 (Guillemette et al, 2015; Lai et al, 2017; Patch et al, 2015; Ray Chaudhuri et al, 2016; Rondinelli et al, 2017). Importantly, it is not clear how these factors would be downregulated in BRCA2 mutant cancers.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that reduced recruitment of the exonuclease MRE11 in BRCA1-deficient cells prevented end resection at these sites and promoted fork stability (Ray Chaudhuri et al, 2016). Reduced recruitment of another DNA exonuclease, MUS81, has also been shown to promote stability of replication forks in BRCA2-deficient cancers that develop resistance to PARP inhibition (Rondinelli et al, 2017). Finally, it has been reported that maintenance of replication forks can be regulated at the transcriptional level.…”
Section: Dna Repair-mediated Resistance Mechanisms To Parp Inhibitionmentioning
confidence: 99%